IL-1β/IL-6/CRP and IL-18/ferritin: Distinct Inflammatory Programs in Infections - Slaats, Jeroen; ten Oever, Jaap; van de Veerdonk, Frank L.; Netea, Mihai G. (PLoS pathogens, 2016)
The host inflammatory response against infections is characterized by the release of pro-inflammatory cytokines and acute-phase proteins, driving both innate and adaptive arms of the immune response. Distinct patterns of circulating cytokines and acute-phase responses have proven indispensable for guiding the diagnosis and management of infectious diseases. This review discusses the profiles of acute-phase proteins and circulating cytokines encountered in viral and bacterial infections. We also propose a model in which the inflammatory response to viral (IL-18/ferritin) and bacterial (IL-6/CRP) infections presents with specific plasma patterns of immune biomarkers.